Uzbekistan : Energy/Power Sector Issues Note - Kochnakyan, Artur; Khosla, Sunil Kumar; Buranov, Iskander; Hofer, Kathrin; Hankinson, Denzel; Finn, Joshua (World Bank, Washington, DC, 2014)
This note focuses on the energy and power sector in Uzbekistan with the purpose of identifying some of the key issues faced by the sector and outlining potential solutions. In particular, the note aims to inform the Government thinking by providing input on priorities in the sector. The note also outlines potential solutions the Government may want to consider to address the identified challenges in the short and longer time and highlights the areas where the Government can start acting immediately. The analysis is based on the information and data provided by the Government during preparation of the Bank's investment lending operations, other analytical work as well as data/information collected from public sources. The note is structured as follows: section one discusses the importance of the energy sector to the economy and provides an overview of the sector. Section two provides a more detailed overview of the power sector. Section three identifies the principal challenges in the power sector. Section four proposes potential solutions to address these challenges. Finally, section five outlines a potential role for the World Bank in supporting the Government to address power sector challenges.